Matrix reorganization with intramolecular tunneling of H atom: Formic acid in Ar matrix - Trakhtenberg, Leonid I.; Fokeyev, Anatoly A.; Zyubin, Alexander S.; Mebel, Alexander M.; Lin, S. H. (My University, 2009)
The intramolecular tunneling of hydrogen atom in formic acid HCOOH at low temperatures is considered based on literature experimental data on C-O internal rotation. The energetic and geometric parameters as well as vibrational frequencies for formic acid in cis and trans configurations surrounded by 12 Ar atoms are calculated in the frame of the MP2 approach with extended basis sets. The temperature and pressure dependence of the rate constant is analyzed taking into consideration the matrix reorganization for the Debye model of lattice motion. It has been shown that the available experimental data can be explained by the suggested matrix reorganization mechanism. Theoretical expressions for the temperature dependence of the rate constant agree well with the experimental data on the cis to trans tunneling reactions in formic acid with fitting parameters attaining reasonable values. A mechanism describing pressure dependence of the rate constant for H-atom intramolecular tunneling reactions is also proposed.
Keywords: argon; Debye temperature; hydrogen; organic compounds; perturbation theory; reaction rate constants; rotational isomerism; vibrational states